Few-shot Learning: Methods and Applications - Li Jiaxiang; Li Mingyang (ITM Web of Conferences)
The Few-shot learning (FSL) approach distills meaningful features from a constrained sample set, allowing models to swiftly adjust to novel tasks and decreasing the dependency on extensive datasets. This approach leverages methods involving meta-learning, transfer learning, and data augmentation to boost the model's ability to recognize new categories. In many areas of artificial intelligence, obtaining large annotated datasets is often high in financial demand and extensively time-consuming, particularly in specialized fields with limited data availability. Therefore, the study of FSL is particularly critical. This paper first reviews the relevant methods of FSL, primarily categorizing them into model fine-tuning based FSL, data augmentation-based FSL, and transfer learning-based FSL. Model fine-tuning based FSL involves making slight adjustments to pre-trained models, allowing them to adapt to new tasks. Data augmentation-based FSL enhances the model's generalization ability by generating or expanding existing data. Transfer learning-based FSL transfers knowledge acquired by models from large datasets to smaller ones, enhancing the learning outcomes. Subsequently, this paper reviews the application areas of FSL and explores its impact in these fields. This paper aims to present the current state and prospects of this technique, providing valuable insights for researchers in related fields.